2013
DOI: 10.1177/1099636213487004
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the flexural properties of balsa and polymer foam core sandwich structures: Influence of core type and contour finishing options

Abstract: Polymer foams are frequently used as core materials in sandwich structures for applications such as aerospace, naval, and wind industry. It is known that the core material contributes to the overall mechanical properties of these sandwich structures up to a remarkable extent. In addition, due to the curvature and geometrical complexities of several applications, these cores are available with special cuts/grooves (finishing options) to provide bendability and better resin infusion during processing. The goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 14 publications
2
55
0
1
Order By: Relevance
“…PET foams are becoming more attractive as sandwich core materials due to some key advantages and therefore could compete with more traditional foams of PVC, PU, and PS [54]. Although PET foams could possess good fatigue resistance [67], their static strength and moduli are usually lower than those of PVC foams at comparable densities. In addition, PET foam cores can be thermally bonded to thermoplastic face sheets to make full thermoplastic sandwich structures with improved impact properties.…”
Section: Pet Foammentioning
confidence: 99%
See 1 more Smart Citation
“…PET foams are becoming more attractive as sandwich core materials due to some key advantages and therefore could compete with more traditional foams of PVC, PU, and PS [54]. Although PET foams could possess good fatigue resistance [67], their static strength and moduli are usually lower than those of PVC foams at comparable densities. In addition, PET foam cores can be thermally bonded to thermoplastic face sheets to make full thermoplastic sandwich structures with improved impact properties.…”
Section: Pet Foammentioning
confidence: 99%
“…There are a few works [13,[67][68][69], though, which make correlations between foam cell structure and the resulting compression and shear properties. There are a few works [13,[67][68][69], though, which make correlations between foam cell structure and the resulting compression and shear properties.…”
Section: Pet Foammentioning
confidence: 99%
“…One of its main advantages is its ability to absorb energy. Balsa wood is also among the most frequently studied bio-based cores due to its high specific compressive and shear properties [10][11][12]. It has often been used in marine applications reinforced with GFRP [13].…”
Section: Introductionmentioning
confidence: 99%
“…The deformation and failure characteristics of the foam core play a very important role in determining the mechanical performance of the sandwich structure. Hence, many research studies [9][10][11][12][13][14][15][16][17][18] have explored new types of sandwich structures by changing the type and density of the material used for the core.…”
Section: Introductionmentioning
confidence: 99%
“…Juntikka and Hallstrom [12] reported that the shear modulus, shear strength and shear strain at failure of sandwich structures were all affected by the choice of the density for the core material. Fathi et al [13,14] investigated the effect of the type of core material employed on the flexural properties of the sandwich structure for four different core materials made from PVC, poly(ethylene terephthalate) (PET), polyurethane (PU) and balsa wood, with skins of GFRP. All of these different types of sandwich structures were evaluated under four-point bend loading and it was found that the balsa-wood core imparted the highest shear strength.…”
Section: Introductionmentioning
confidence: 99%